2022
DOI: 10.3389/fphys.2022.880158
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Characterization of a Red Light-Activated Vasodilation: A Photobiomodulation Study

Abstract: Nitric oxide dependent vasodilation is an effective mechanism for restoring blood flow to ischemic tissues. Previously, we established an ex vivo murine model whereby red light (670 nm) facilitates vasodilation via an endothelium derived vasoactive species which contains a functional group that can be reduced to nitric oxide. In the present study we investigated this vasodilator in vivo by measuring blood flow with Laser Doppler Perfusion imaging in mice. The vasodilatory nitric oxide precursor was analyzed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Light therapy in the visible range spectrum can affect photosensitive molecules, such as ATP, superoxide dismutase, or cytochrome C oxidase, which then affect the redox balance in the cells [ 11 , 12 , 13 ]. Current studies suggest that light therapy leads to an increase in mitochondrial activity, ROS production, as well as NO and, therefore, in vasodilation [ 11 , 34 , 35 , 36 ]. We did not find that light therapy had any significant effects on systolic blood pressure (SBP) or diastolic blood pressure (DPB).…”
Section: Discussionmentioning
confidence: 99%
“…Light therapy in the visible range spectrum can affect photosensitive molecules, such as ATP, superoxide dismutase, or cytochrome C oxidase, which then affect the redox balance in the cells [ 11 , 12 , 13 ]. Current studies suggest that light therapy leads to an increase in mitochondrial activity, ROS production, as well as NO and, therefore, in vasodilation [ 11 , 34 , 35 , 36 ]. We did not find that light therapy had any significant effects on systolic blood pressure (SBP) or diastolic blood pressure (DPB).…”
Section: Discussionmentioning
confidence: 99%
“…Coupling the observations that IR-induced relaxations were largely endothelium-dependent and blocked by ODQ certainly suggests that the primary mechanism of action underlying IR-induced relaxation of the occipital artery segments involves the actions of nitric oxide/S-nitrosothiols that elicit their effects via the activation of soluble guanylate cyclase and the generation of cGMP. Red/near IR light is reported to stimulate Ca 2+ influx and Ca 2+ release from the endoplasmic reticulum ( Golovynska et al, 2020 ) degradation of preformed endothelial pools of S-nitrosothiols to nitric oxide ( Keszler et al, 2017 ; Keszler et al, 2018 ; Keszler et al, 2019 ; Weihrauch et al, 2021 ; Keszler et al, 2022 ), and release of S-nitrosothiol-containing vesicles into the interstitial space ( Riego et al, 2009 ). However, light in this wavelength has very low absorbance by water, meaning heat is not a likely mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The direct application of IR light to neural tissues can elicit a spatially selective inhibition ( Duke et al, 2013 ; Lothet et al, 2017 ), and the extracellular ion concentration can modulate the sensitivity of neural tissues to IR light ( Zhuo et al, 2021 ). There is compelling evidence that the application of red/near IR elicits endothelium-dependent vasodilation in murine facial arteries ( Keszler et al, 2017 ) and hindlimb ( Keszler et al, 2022 ), and that this vasodilation may involve the release of nitric oxide from pre-formed pools of S-nitrosothiols and/or nitrosylated proteins ( Keszler et al, 2018 ; Keszler et al, 2019 ; Weihrauch et al, 2021 ). Based on the evidence in other arteries, it may be possible that these pre-formed pools of S-nitrosothiols in murine facial arteries are stored within cytoplasmic vesicles that are subject to exocytosis ( Seckler et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…This bilateral response has importance in clinical practice when the area requiring treatment is not accessible or is too painful to treat. Although the vasodilative response following PBM was shown to depend on local NO synthesis or release ( Samoilova et al, 2008b ; Keszler et al, 2018 ; Weihrauch et al, 2021 ; Keszler et al, 2022 ), it has been suggested that the bilateral effect may also point to the involvement of neuronal pathways coursing through the central nervous system ( Koltzenburg et al, 1999 ) and/or the systemic release of a humoral mediator. Previous clinical studies using other interventions also observed bilateral effects where local stimulation on one side affected the other side ( Koltzenburg et al, 1999 ; Huang et al, 2007 ; Ovadia-Blechman et al, 2018 ; Ovadia-Blechman et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…PBM was shown to stimulate vasodilatation and increase peripheral blood flow ( Schindl et al, 1998 ; Schindl et al, 2002 ; Samoilova et al, 2008a ; Samoilova et al, 2008b ). This effect is based at least in part on the upregulation by PBM of synthesis and secretion of nitric oxide (NO) and modification of reactive oxygen species ( Vladimirov et al, 2000 ; Chen et al, 2008 ; Gavish et al, 2008 ; Chen et al, 2022 ; Keszler et al, 2022 ). In a previous study using laser Doppler flowmetry and thermal imaging, PBM was found to increase microvascular flow ( Gavish et al, 2020 ) and that those that did not respond were found to have either ‘hot’ or ‘cold’ hand with skin temperature at baseline being >37.5°C or <33°C respectively ( Gavish et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%